Analysis of the positioning of the head, trunk, and upper limbs during gait in children with visual impairment - Sankako, Andréia Naomi [UNESP]; Lucareli, Paulo Roberto Garcia; Carvalho, Sebastião Marcos Ribeiro de [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (De Gruyter, 2014)
Background: This study analyzed the positioning of the head, trunk, and upper extremities during gait in children with visual impairment. Methods: A total of 11 children participated in this study: 6 with blindness and 5 with low vision. The kinematics of the positioning of the head, trunk, shoulders, and elbows in each participant was analyzed during the four phases of the gait cycle: foot strike, support, toe-off, and swing. Results: There were significant differences between children with blindness and low vision in the positioning of the trunk in the sagittal plane during the foot strike, support, and swing phases. Conclusions: The analysis identified postural alterations of the head, trunk, shoulder, and elbow during the children’s gait, highlighting the relevance of appropriate stimulation at an early age in orientation and mobility programs, as well as the essential presence of professionals who work with movement.
Keywords: deficiência visual; orientação e mobilidade